Rozmówki polsko-hiszpańskie. Problemy językowe i próby ich przezwyciężenia podejmowane przez polskich uczestników hiszpańskiej wojny o niepodległość w świetle materiałów wspomnieniowych - Krzyżostaniak, Magdalena (Annales Universitatis Paedagogicae Cracoviensis | Studia Historicolitteraria, 2021)
The article presents selected mechanisms of communication between the Polish participants of the Napoleonic campaign in 1808-1812 and the local population behind the Pyrenees. The sources of information were the memoirs of Polish soldiers fighting on the Iberian Peninsula in the Grande Armée. Even though a significant part of the memoirs focuses on the military aspects of the participation of Poles in the Peninsular War, several do provide a whole spectrum of information about the daily lives of soldiers on foreign ground and many observations regarding the customs of their brothers in arms - mainly the French - as well as the local population. Among the fragments devoted to the non-military aspects of their stay on the Iberian Peninsula, the remarks on the attempts at communication - both verbal and non-verbal - between Poles and Spaniards seem to be particularly interesting. The purpose of this article is to explain why, in many situations, efficient communication could not take place in an intermediary language (French) and how the Polish soldiers dealt with lexical and grammatical structures in the previously unknown Spanish language. It is worth pointing out that language transfer is clearly noticeable - both from the native language of the soldiers (Polish) and from French, which most of Napoleonic soldiers learnt as their first Romance language.